Timing of combination antiretroviral therapy (cART) initiation is not associated with stillbirth among HIV‐infected pregnant women in Malawi. Issue 6 (1st April 2019) - Msukwa, Malango T.; Keiser, Olivia; Jahn, Andreas; van Oosterhout, Joep J.; Edmonds, Andrew; Phiri, Nozgechi; Manjomo, Ronald; Davies, Mary‐Ann; Estill, Janne
Abstract: Objective: To assess the association between timing of maternal combination ART (cART) initiation and stillbirth among HIV‐infected pregnant women in Malawi's Option B+ programme. Methods: Cohort study of HIV‐infected pregnant women delivering singleton live or stillborn babies at ≥28 weeks of gestation using routine data from maternity registers between 1 January 2012 and 30 June 2015. We defined stillbirth as death of a foetus at ≥28 weeks of gestation. We report proportions of stillbirth according to timing of maternal cART initiation (before pregnancy, 1st or 2nd trimester, or 3rd trimester or labour). We used logistic regression, with robust standard errors to account for clustering of women within health facilities, to investigate the association between timing of cART initiation and stillbirth. Results: Of 10 558 mother–infant pairs abstracted from registers, 8380 (79.4%) met inclusion criteria. The overall rate of stillbirth was 25 per 1000 deliveries (95% confidence interval 22–29). We found no significant association between timing of maternal cART initiation and stillbirth. In multivariable models, older maternal age, male sex of the infant, breech vaginal delivery, delivery at < 34 weeks of gestation and experience of any maternal obstetric complication were associated with higher odds of stillbirth. Deliveries managed by a mission hospital or health centre were associated with lower odds of stillbirth. Conclusion: Pregnant women's exposure to cART, regardless of time of its initiation, was not associated with increased odds of stillbirth. Abstract : Objectif: Evaluer l'association entre le moment d'initiation de l'ART de combinaison (cART) maternel et la mortinaissance chez les femmes enceintes infectées par le VIH dans le programme Option B+ du Malawi. Méthodes: Etude de cohorte de femmes enceintes infectées par le VIH qui ont accouché de bébés singletons vivants ou mort‐nés à 28 mois ou plus de grossesse, en utilisant les données de routine des registres de maternité entre le 1 er janvier 2012 et le 30 juin 2015. Nous avons défini la mortinatalité comme le décès d'un fœtus à 28 semaines ou plus de gestation. Nous rapportons sur les proportions de mortinatalité selon le moment de l'initiation du cART maternel (avant la grossesse, au 1 er, 2 è ou 3 è trimestre ou durant le travail). Nous avons utilisé une régression logistique, avec des erreurs standards robustes, pour prendre en compte le regroupement des femmes par établissements de santé, afin d'investiguer le lien entre le moment d'initiation du cART et la mortinaissance. Résultats: Sur 10.558 paires mère‐enfant extraites des registres, 8.380 (79, 4%) répondaient aux critères d'inclusion. Le taux global de mortinatalité était de 25 pour 1.000 accouchements (intervalle de confiance à 95%: 22‐29). Nous n'avons trouvé aucune association significative entre le moment de l'initiation du cART maternel et la mortinatalité. Dans les modèles multivariés, l'âge plus élevé de la mère, le sexe masculin du nourrisson, l'accouchement par voie basse, l'accouchement à moins de 34 semaines de gestation et l'expérience de toute complication obstétricale maternelle étaient associés à des probabilités de mortinatalité plus élevées. Les accouchements gérés par un hôpital de la mission ou un centre de santé étaient associés à une probabilité plus faible de mortinatalité. Conclusion: L'exposition des femmes enceintes au cART quel que soit le moment de son initiation, n'a pas été associée à une probabilité accrue de mortinatalité.